EFFORTS OF BHABINKAMTIBMAS THROUGH COUNSELING AND ADMINISTRATION TO PREVENT THE CRIME OF CURANMOR AT KENDAL POLRES - HABIEM RAMADYA (Advances in Police Science Research Journal, 2022)
This writing is motivated by the number of motor vehicle theft crimes that have never decreased at the Kendal Police Station in 2019 to 2021. This is one of the lack of efforts by Bhabinkamtibmas in carrying out coaching and counseling activities as a preventive effort from the police. The purpose of this paper is to explain how the efforts of Bhabinkamtibmas in preventing theft at the Kendal Police using Management Theory and Communication Theory as well as the use of the Binluh Concept, the Effort Concept, the Motor Vehicle Theft Concept, the Binmas Concept, and the Bhabinkamtibmas Concept. This writing uses a qualitative approach which requires the researcher's knowledge in understanding the object of research which aims to describe the implementation of coaching and counseling activities. Data collection techniques are interviews, observations or observations, and document review. The results of this paper indicate that there are factors that influence the efforts of Bhabinkamtibmas, namely Bhabinkamtibmas personnel who are still not optimal in carrying out their duties, the increasing conditions of the Covid-19 pandemic, and the lack of an operational budget. The implementation of guidance and counseling for Bhabinkamtibmas in preventing the crime of motor vehicle theft has not yet achieved the expected goals. Based on the results of the writing, a solution is given to achieve Bhabinkamtibmas efforts through coaching and counseling to prevent the crime of motor vehicle theft through developing the material provided, carrying out routine evaluations and providing Reward and Punishment on Bhabinkamtibmas performance.